2017
DOI: 10.1071/wf17019
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of burn severity at extended temporal scales: a decade of ecosystem response in mixed-conifer forests of western Montana

Abstract: Abstract. We collected field and remotely sensed data spanning 10 years after three 2003 Montana wildfires to monitor ecological change across multiple temporal and spatial scales. Multiple endmember spectral mixture analysis was used to create post-fire maps of: char, soil, green (GV) and non-photosynthetic ( Initial estimates of char and NPV from the HS images were significantly correlated with their ground-measured counterparts (r ¼ 0.60 (P ¼ 0.03) and 0.68 (P ¼ 0.01) respectively), whereas HS GV and Landsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 76 publications
1
12
0
Order By: Relevance
“…Edwards et al (2015) did not find significant differences in understory green cover between burn severity classes in sub-boreal conifer forest in British Columbia, Canada, five to six years after an experimental burn. A remote sensing study by Lewis et al (2017), on some of the same Montana fires as in this study, suggested that, 10 years post fire, green cover had increased to approximately 60% regardless of initial condition, but that this took about twice as long on high burn severity sites. Remote sensing studies have also shown that Net Primary Productivity (NPP) in North American boreal forests has returned to pre-fire levels nine years following fire (Hicke et al 2003).…”
Section: Green Cover Along a Burn-severity Gradient (Hypothesis 1d)supporting
confidence: 48%
“…Edwards et al (2015) did not find significant differences in understory green cover between burn severity classes in sub-boreal conifer forest in British Columbia, Canada, five to six years after an experimental burn. A remote sensing study by Lewis et al (2017), on some of the same Montana fires as in this study, suggested that, 10 years post fire, green cover had increased to approximately 60% regardless of initial condition, but that this took about twice as long on high burn severity sites. Remote sensing studies have also shown that Net Primary Productivity (NPP) in North American boreal forests has returned to pre-fire levels nine years following fire (Hicke et al 2003).…”
Section: Green Cover Along a Burn-severity Gradient (Hypothesis 1d)supporting
confidence: 48%
“…Other researchers have found significant correlations between field-measured ground cover and MESMA predicted fractional cover [5,65]. These broad fractional cover classes (their presence or absence as well as their condition) can indicate first-order fire effects on vegetation and soil [66].…”
Section: Fire Effectsmentioning
confidence: 99%
“…These broad fractional cover classes (their presence or absence as well as their condition) can indicate first-order fire effects on vegetation and soil [66]. They can also be monitored as second-order fire effects, such as vegetation recovery over time [5,67]. Residual litter, newly deposited needlecast and downed woody debris provide protection to soils from wind-and water-driven erosion [68].…”
Section: Fire Effectsmentioning
confidence: 99%
See 2 more Smart Citations